Peran Green Library dan Perpustakaan Islam dalam Pengembangan Ilmu Pengetahuan - Kesuma, Aghesna Rahmatika; Rahmawati, Dwi Indri; Putri, Mutiara Cahyani (UIN Raden Intan Lampung, 2022)
Human civilization is characterized by the existence of a writing culture, since the discovery of human letters began to write starting from writing using stones, leaves, palm stems and other writing lats that existed at that time. From these writings which are then stored in the library which becomes a legacy for future generations. During the classical Islamic period, libraries experienced very rapid development, starting from the many libraries that were built magnificently and equipped with adequate facilities. During the classical Islamic era there were several types of libraries, one of which was the public library. The public library itself was built to be shown to the general public around the library. Islamic libraries are very closely related to science, so libraries have an important role in the development of science, such as; as an information center or learning center, as a research center, and as a translation center. Green Library also acts as an environmentally friendly library (cool, fresh, beautiful, beautiful) which is far from damaging the environment so that learning and working activities become more comfortable and enthusiastic.